REDESIGN APLIKASI SAMSAT MOBILE JAWA BARAT (SAMBARA) MENGGUNAKAN USER CENTERED DESIGN (UCD). - Diki Alawi Nurfalah; Meriska Defriani; Imam Ma'ruf Nugroho (POLITEKNIK PIKSI GANESHA, 2023)
easier for people to carry out their obligations as citizens, namely paying vehicle taxes, not only that, in the application there is information about the Mobile Samsat schedule, ownership protection, and other menus related to vehicles. In the use of user experience (UX) applications and the appearance of the interface (UI) is one of the factors that affect the success or failure of the e-government system itself, questionnaires are distributed using the System usbaility Scale (SUS) and Usbaility testing methods to determine the level of usability of the application and the problems experienced by users. There are problems experienced by users when using the SAMBARA application including not appearing samling schedule, not getting a payment code to continue payment, and there is an icon that is too small on the samling info menu. This study aims to help SAMBARA application users to be more comfortable when used, In this study using the User Centered Design (UCD) method which is used as a redesign of the user interface and user experience, and System Usability Scale (SUS) as an initial usability test. This research resulted in a new SAMBARA application display and obtained an average result of SUS 74.83 and classified as grade scale B and acceptable to users.